Penerapan Terapi Hypnobirthing untuk Menurunkan Tingkat Ansietas dan Gangguan Pola Tidur pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Putri Ayu, Kota Jambi - Nababan, Eva Daya; Mutmainnah, Muthia (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2024)
Anxiety often appears in the third trimester of pregnancy. Pregnant women may feel anxious about their baby's and their own life, worry that the baby will be born prematurely or abnormally, and fear the pain and physical dangers of childbirth. These anxieties often lead to sleep difficulties. Hypnobirthing therapy is an alternative complementary therapy that can help pregnant women feel more comfortable and relaxed. The objective of the research is to determine the effects of Hypnobirthing therapy in reducing anxiety and sleep disturbances in third-trimester pregnant women in the Putri Ayu Health Center, Jambi City. The method involves applying Hypnobirthing therapy to these women. The results show that after three days of Hypnobirthing relaxation therapy, anxiety levels decreased, as evidenced by the reduction in the Perinatal Anxiety Screening Scale (PASS) score from 23 (moderate anxiety) before the intervention to 8 (mild anxiety) after the intervention. Additionally, sleep pattern disturbances were resolved. The conclusion is that Hypnobirthing therapy is effective in reducing anxiety levels and sleep disturbances in third-trimester pregnant women. It is recommended that health workers apply Hypnobirthing therapy to help manage anxiety and sleep issues in pregnant women.